Formation of 10/12/14‐Membered Rings is Favored over 5/6/7‐Membered. An Unexpected Result from Oxazole Chemistry. Issue 30 (1st August 2019) - Slobodyanyuk, Evgeniy Y.; Berezowska, Yulia L.; Solomin, Vitaliy V.; Volochnyuk, Dmitriy M.; Rozhenko, Alexander B.; Ryabukhin, Sergey V.; Grygorenko, Oleksandr O.
Abstract : Base‐promoted cyclization of N ‐Boc ‐ω ‐(4‐(chloromethyl)oxazol‐5‐yl)alkylamines led to the corresponding "dimerization" products containing fused 10‐, 12‐, and 14‐membered rings. Experimental data showed that the formation of these ring systems is favored over the corresponding 5‐/6‐/7‐membered ones, which was partially confirmed by DFT calculations; this effect was especially significant in the case of the 5‐/10‐membered pair. Abstract : Base‐promoted cyclization of N ‐Boc ‐ω ‐(4‐(chloromethyl)oxazol‐5‐yl)alkylamines results in preferable formation of fused 10‐, 12‐, and 14‐membered rings over the corresponding 5‐, 6‐, and 7‐membered ones.